ASPEK YURIDIS PENYELESAIAN SENGKETA KEPEGAWAIAN MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Suswoto Suswoto (Universitas Janabadra, 2017)
Civil servants as civil state apparatus is one of the tools or facilities of the state in performing its functions to achieve the national goals. For that required adequate arrangements to be obtained professional civil state apparatus, clean from collusion, corruption and nepotism and able to provide maximum public service for society and carrying out governmental and developmental tasks. In carrying out duties and functioni it is not infrequent clashes and disputes that cause employment disputes. The settlement of personnel congress is in fact both in the old Personnel Law and in the ASN Act has been regulated separately in order to provide protection law against ASN, however, because both institutions such as ASN Advisory Board in charge of resolving disputes and regulations derived from the Act of ASN has not been made , so that procedures for dispute resolution of personnel still use the old institutions and regulations such as the Employment Advisory Board.Keywords: Settlement, Dispute, Personnel Affairs, Civil State Apparatus